Comparison of RO tropopause height based on different tropopause determination methods - Liu, Ziyan; Sun, Yueqiang; Bai, Weihua; Xia, Junming; Tan, Guangyuan; Cheng, Cheng; Du, Qifei; Wang, Xianyi; Zhao, Danyang; Tian, Yusen; Meng, Xiangguang; Liu, Congliang; et al. (Advances in space research, 2021)
The tropopause is an important boundary in the Earth’s atmosphere, and has been the subject of close attention from atmosphere and climate researchers. To monitor the global tropopause using radio occultation (RO) data, there are two primary methods, one is the widely used temperature lapse rate method, and the other is the bending angle covariance transform method which is unique to RO data. We use FengYun3-C (FY3C) and Meteorological Operational Satellite Program (MetOp) RO data and European Centre for Medium-Range Weather Forecasts (ECMWF) operational analysis data to determine differences in RO tropopause height calculated by these two methods. We compute biases of the RO lapse rate tropopause height (LRTH) and the RO bending angle tropopause height (BATH) relative to the ECMWF LRTH. The dependences of the tropopause height biases on tropopause height (TPH) retrieval method, latitude, season and RO mission are investigated. The results indicate that BATH show a consistent 0.8–1.2 km positive bias over the tropics and high latitude regions compared with LRTH, however, over 25° to 40° latitude in both hemisphere, BATH results are less stable. Furthermore, the mean bias between BATH and LRTH displayed a different symmetrical characteristic from 2017.12 to 2018.2 (DJF) compared to 2018.6–2018.8 (JJA). However, except for some bias over Antarctica, the mean value of both LRTH and BATH show a similar tropopause variation, indicating the consistency of both methods.